2020
DOI: 10.1155/2020/5947680
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy and Precision of the Continuously Stored Data from Flash Glucose Monitoring System in Type 2 Diabetes Patients during Standard Meal Tolerance Test

Abstract: Background. The purpose of this study was to investigate the accuracy of the continuously stored data from the Abbott FreeStyle Libre flash glucose monitoring (FGM) system in Chinese diabetes patients during standard meal tests when glucose concentrations were rapidly changing. Subjects and Methods. Interstitial glucose levels were monitored for 14 days in 26 insulin-treated patients with type 2 diabetes using the FGM system. Standard meal tests were conducted to induce large glucose swings. Venous blood gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…Continuous glucose monitoring readings have been reported to be lower than PG (Yardley et al, 2013;Yan et al, 2020). Consistently, FGM readings were 0.8-1.2 mmol•L −1 lower than PG during postmeal sitting and walking conditions in the present study (Supplementary Table 1).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Continuous glucose monitoring readings have been reported to be lower than PG (Yardley et al, 2013;Yan et al, 2020). Consistently, FGM readings were 0.8-1.2 mmol•L −1 lower than PG during postmeal sitting and walking conditions in the present study (Supplementary Table 1).…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, the Bland-Altman method and the Clarke error grid analysis showed that the FGM values were clinically acceptable (Figures 3, 4). In previous studies, almost 100% of the value pairs fell within zones A and B of the Clarke error grid analysis (Bally et al, 2016;Moser et al, 2016;Biagi et al, 2018;Yan et al, 2020). This excellent, clinically acceptable accuracy proved that the CGM accuracy during postmeal resting and walking was high and was further verified using the Bland-Altman method and Pearson's correlation analysis.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Considering the low MARD found in our study, it can be concluded that isCGM tracks post-prandial glucose excursions accurately in situations of nutritionally induced rapid glucose changes. Although performed in people with type 2 diabetes, similar findings were found during standard meal tests, detailing that 100% of isCGM comparison points were falling within zones A and B of the Clarke and Parkes error grid analysis accompanied by a MARD of 10.7% [ 15 ]. However, in this study, it was also found that, during rapidly changing glucose concentrations, the MARD increased to 19.0%, which exceeds the number observed in our (very) high RCPG.…”
Section: Discussionmentioning
confidence: 72%
“…Therefore, the high rate of hypoglycemic episodes in Group 1 is unexpected. Although flash CGM technology was proven to be accurate in comparison to capillary-blood glucose tests [ 30 ], technical limitations include a period of 12 h after placing the senso when flash CGM readings are unreliable [ 31 ], inaccurate CGM values during rapid excursions of blood glucose [ 32 ] and during exercise [ 33 ]. Overall, the accuracy of flash CGM was shown to be slightly lower in the hypoglycemic range, though more hypoglycemic episodes were detected [ 34 ].…”
Section: Discussionmentioning
confidence: 99%